“COSTUME WORLD” IN THE NOVEL “PRINCE SEREBRYANY” BY A. K. TOLSTOY. - MARTIRYAN, NAIRA (Bulletin of Yerevan University H: Russian Philology, 2020)
The article considers costume as a phenomenon of culture. The article analyses the "costume" characteristics of the heroes and the main functions of it in the historical novel "Prince Serebryany" (“The Silver Prince”) by A. K. Tolstoy. The analysis of the “costume world” of the novel shows that the costume layer of A. K. Tolstoy's work is ambiguous since clothing serves as a means of characterizing not only the hero but also the era, the relationship between people. It depends on etiquette and, at the same time, determines the behavior, and reflects the author’s concept of history.
Keywords: gender, historicism, carnivalization, costume, communication, culture, status